Analisis Tantangan dan Peluang Digitalisasi Instrumen Pasar Uang Terhadap Efektivitas Transmisi Kebijakan Moneter - Jalu Raden Al-Awwali; Muhammad Iqbal; Dwi Dzikri Al Faris Ascha; Muhammad Yusuf Bahtiar (Indonesia Economic Journal, 2026)
The money market plays a very crucial role as the primary channel in the monetary policy transmission system to achieve macroeconomic stability. This study aims to analyze in depth the various challenges and opportunities arising from the digitalization process of money market instruments on the effectiveness of monetary policy transmission in Indonesia. By applying a qualitative descriptive method based on literature study. research data were collected from various scientific literatures, monetary authority reports, and regulations regarding financial technology. The research results show that the digitalization of money market instruments offers great opportunities including increased real-time market transparency, transaction cost efficiency, and acceleration of the interest rate pass-through mechanism to the real sector. However, this digital transformation also brings significant challenges including cybersecurity risks, potential for high liquidity volatility, and the urgency of more responsive.